Experimental analysis of a low controlling voltage tri-electrode MEMS electrostatic actuator for array applications. (16th February 2023) - Allameh, Mehdi; Zhou, Yu; Chen, Tao; Chrusch, Dwayne; Park, Byoungyoul; Shafai, Cyrus
Abstract: A tri-electrode electrostatic actuator with one moving microelectromechanical systems (MEMS) electrode and two stationary electrodes (tri-electrode actuator topology) is experimentally tested in this article. The stationary controlling (intermediate) electrode is perforated and below the moving MEMS electrode, and the common electrode is further below. Numerical simulations were performed to discover the most optimum tri-electrode design parameters to enable the best performance improvement compared to a conventional two electrode electrostatic actuator. A silicon-based moving MEMS electrode was designed with a relatively linear spring constant, and the controlling intermediate and primary stationary electrodes were fabricated on either side of a quartz substrate instead of free space to simplify their fabrication. The measurement results showed that the tri-electrode topology can control the displacement of the MEMS with a lower controlling voltage and with extended controllable range before pull-in instability, compared to the conventional actuator. Simulations and measurements showed the controlling voltage was decreased by 2.6 times smaller than the conventional actuator topology using a bipolar driven intermediate electrode, and the controllable deflection range before pull-in was elevated by 33%. This tri-electrode topology offers benefits for applications in need of arrays of electrostatic actuators such as deformable mirrors.